2002
DOI: 10.1007/bf02504959
|View full text |Cite
|
Sign up to set email alerts
|

Student performance and attitudes using personalized mathematics instruction

Abstract: Data from the National Assessment of Educational Progress (1992a, 1992b indicate that mathematics word problems are difficult for students at all age levels in elementary and secondary schools. A major cause of the difficulty appears to be student inability to convert the problems into the math operations that must be performed to solve them (Hart, 1996). Some researchers have also noted that lack of familiarity with word problem structures may also contribute to poor student performance (Mayer, 1982;Rosen, 19… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
24
0
8

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 19 publications
3
24
0
8
Order By: Relevance
“…In Experiment 3, we want to examine another popular approach to personalization, using elements that are familiar and popular with students. Using personally relevant details-information from background experiences, friends and teachers as characters, favorite topics-has been shown in numerous studies to increase interest, understanding, and reasoning (Anand & Ross, 1987;Lepper & Cordova, 1992;Ku & Sullivan, 2002;López & Sullivan, 1991, 1992. Even characters and objects that come from an interesting fantasy context (i.e., pirates, spaceships) show similar boosts to motivation and learning (Cordova & Lepper, 1996;Parker & Lepper, 1992).…”
Section: Experiments 3: Specific Familiar Popular Charactermentioning
confidence: 99%
“…In Experiment 3, we want to examine another popular approach to personalization, using elements that are familiar and popular with students. Using personally relevant details-information from background experiences, friends and teachers as characters, favorite topics-has been shown in numerous studies to increase interest, understanding, and reasoning (Anand & Ross, 1987;Lepper & Cordova, 1992;Ku & Sullivan, 2002;López & Sullivan, 1991, 1992. Even characters and objects that come from an interesting fantasy context (i.e., pirates, spaceships) show similar boosts to motivation and learning (Cordova & Lepper, 1996;Parker & Lepper, 1992).…”
Section: Experiments 3: Specific Familiar Popular Charactermentioning
confidence: 99%
“…While the personalised instruction students were more influenced by the context of the word problem than their non-personalised instruction counterparts, the personalised and non-personalised groups" students did differ on their attitudes toward mathematics word problem as a male domain. Ku and Sullivan (2002) researched the effects of personalisation on 136 fourth grade Taiwanese students and their teachers. The results of their study revealed that students in the personalised treatment made significantly greater pretest-to-post test gains than those in the non-personalised treatment.…”
Section: Introductionmentioning
confidence: 99%
“…With regard to the attitude variable, only few studies have investigated the effectiveness of personalisation of instruction on students' attitudes toward mathematics word problem and a common conclusion in these studies has been that personalisation of instruction is effective in fostering positive attitudes toward mathematics word problem (Awofala, 2010;Ku & Sullivan, 2002;Lopez & Sullivan, 1992). While research has not focused on the effect of personalisation of instruction on the individual dimension of attitudes toward mathematics word problem, the potential of personalisation of instruction has not been adequately explored in relation to its effect on attitudes toward mathematics word problem in Nigeria as most studies conducted in the country have been centred on achievement, interest, and self-efficacy.…”
Section: Introductionmentioning
confidence: 99%